Two distinct vitellogenin genes are similar in function and expression in the bigfin reef squid Sepioteuthis lessoniana. Issue 5 (12th June 2018) - Chen, Chih; Li, Hau-Wen; Ku, Wei-Lun; Lin, Chien-Ju; Chang, Ching-Fong; Wu, Guan-Chung
Abstract: Unlike vitellogenin, which is the sole major precursor of yolk protein in all oviparous vertebrates, a variety of major precursor of yolk proteins are found among oviparous invertebrates. Sea urchins have a transferrin-like yolk protein, while all other major precursors of yolk proteins in oviparous invertebrates belong to the superfamily of large lipid transfer proteins (LLTPs). However, a comprehensive understanding of vitellogenesis is absent in cephalopods. To understand control of vitellogenesis by the LLTPs gene, two vitellogenins ( VTG1 and VTG2 ), two apolipophorins ( APOLP2A and APOLP2B ), and a cytosolic large subunit of microsomal triglyceride transfer protein ( MTTP ) found in the bigfin reef squid. Only the two VTGs showed high levels of expression in mature females compared to males. We further analyzed the expression profile and localization of both VTGs /VTGs during ovarian development. Our data showed that VTGs /VTGs expressions were correlated to the female reproductive cycle. Ovarian VTG1 and VTG2 were localized in the follicle cells but not in oocytes. In addition, VTG1 and VTG2 were represented in follicle cells and oocytes. Thus, our results showed that both VTGs were synthesized by follicle cells and are then delivered to oocytes. In addition, we demonstrated that VTGs were the major precursor of yolk protein in bigfin reef squid. We also found differential proteolytic cleavage processes of VTG1 and VTG2 during VTGs accumulation in oocytes. Therefore, our data shed light on the molecular mechanism of the yolk accumulation pathway in cephalopods. Abstract : Two distinct vitellogenins, which are synthesized by the follicle cells, are the major precursor of yolk protein of oocytes in bigfin reef squid.